El mundo de ayer: la monarquía hispánica: Aspectos filosóficos del orden político-jurídico de la Modernidad católica - Pena-Búa, Pilar (Cauriensia, 2023)
This paper analyses the philosophical aspects that ground the conception of power in the Hispanic Monarchy. This conception is the product of the renovation of the Catholic thought brought forth by the Spanish authors during the 16th and 17th centuries, which led to a Catholic modernity apart from the political and philosophical universe produced by the Reformation and the Enlightenment.